Edukasi Kebutuhan Nutrisi dan Senam Hamil Pada Ibu Hamil - Puspasari, Ike Hesti; Tusi Eka Redowati; Tri Susanti (LPPM UNINUS, 2025)
Abstract The community service program, which included education on nutritional needs and prenatal exercise for pregnant women, aimed to increase mothers' knowledge in an effort to improve their health and nutritional status, as well as fitness during pregnancy, which impacts the child's health and well-being. The target group for this community service activity was pregnant women in Sukoharjo Village. The community service program consisted of a pre-test in the form of a questionnaire, followed by counseling on prenatal exercise, and finally, a post-test in which all pregnant women completed a questionnaire. After the education, the results showed an increase in pregnant women's knowledge about nutrition and the benefits of prenatal exercise as an effort to prevent complications and cope with childbirth. Keywords: Nutritional Needs, Prenatal Exercise, Counseling, Pregnant Women